Clutter covariance matrix estimation using weight vectors in knowledge‐aided STAP. Issue 8 (1st April 2017) - Jeon, H.; Chung, Y.; Chung, W.; Kim, J.; Yang, H.
Abstract : A knowledge‐aided space–time adaptive processing (STAP) is a quite useful technique to suppress non‐stationary and heterogeneous clutter. It estimates a covariance matrix by combining a conventional covariance matrix based on secondary data with a synthesised one by prior information. A new combining method is presented, where weight vectors, rather than constant weights, are used to combine two covariance matrices. In this method, the weight vectors are derived in a way to maximise clutter‐to‐noise ratio of the combined covariance matrix. A numerical simulation is conducted for a bistatic radar scenario where clutter non‐stationarity and heterogeneity can be assumed and the performance of the proposed method is demonstrated in terms of clutter suppression and target detection.